Waste Generation from Inbound Tourism in Galicia - Carrascal Incera, , André; Fernández Fernández, , Melchor; Pereira López, , Xesús (Revista Galega de Economía)
Estimating the impact of tourism on an economy means to estimate both benefits and costs associated with tourism. Without any doubt, tourism has a huge economic and social importance. However, the growth of tourism has been accompanied by significant drawbacks in terms of emission of greenhouse gases, water consumption, untreated water, physical waste, damage to terrestrial and marine biodiversity or threat to the survival of culture and traditions. Most of the economic analyses of tourism impacts are focused on the benefits of the expenditure of the visitors, without taking into account the existence of indirect impacts or environmental effects.The aim of this article is to make an approach to the environmental impact of tourism through an estimation of the waste generation from the consumption of non-residents. To satisfy the touristic final demand vector the economy needs to produce a range of goods and services. During this production we get not only goods but also physical waste that we return to the environment. Through an extension of the traditional input-output model, it is possible to obtain the waste generated directly and indirectly by the consumption of non-resident visitors. For practical purposes, we apply the model to the Galician economy.